2010
DOI: 10.1007/s11606-010-1475-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Screening and Risk of Postoperative Complications in Male VA Patients Undergoing Major Non-cardiac Surgery

Abstract: AUDIT-C scores of 5 or more up to a year before surgery were associated with increased postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 46 publications
3
74
1
3
Order By: Relevance
“…Further, while the present study had too few women to enable stratified analyses, future research should be stratified by gender when possible. The VASQIP database does not comprehensively capture patient factors, such as other substance use, mental health diagnoses, and socioeconomic determinants, which are known to be associated with unhealthy alcohol use and may also influence post-operative complications (18,43). Similarly, laboratory measures that may be associated with alcohol use and surgical complications, such as tests of liver function and coagulopathy, are not consistently available in VASQIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, while the present study had too few women to enable stratified analyses, future research should be stratified by gender when possible. The VASQIP database does not comprehensively capture patient factors, such as other substance use, mental health diagnoses, and socioeconomic determinants, which are known to be associated with unhealthy alcohol use and may also influence post-operative complications (18,43). Similarly, laboratory measures that may be associated with alcohol use and surgical complications, such as tests of liver function and coagulopathy, are not consistently available in VASQIP.…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy alcohol usethe spectrum from drinking above national recommended limits to meeting diagnostic criteria for alcohol use disorders (17)-is known to be associated with complications of various surgical procedures (18)(19)(20)(21)(22). Further, it is possible that reduction of alcohol use in the perioperative period may mitigate risk (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Več tujih raziskav je pokazalo, da zdravstvenovzgojni programi med hospitalizacijo pozitivno vplivajo na zmanjšanje simptomov, krajši čas hospitalizacije in splošno dobro počutje pri pacientih s kroničnimi obolenji (Thomsen, et al, 2009;Bradley, et al, 2011;Prorok, et al, 2015). Pacienti, ki so prejeli razumljive zdravstvenovzgojne nasvete, so pogosteje imeli občutek aktivne vključenosti v zdravljenje (Farkaš-Lainščak, 2011;Brady, et al, 2013).…”
Section: Uvodunclassified
“…[30] A study of over 9,000 Veterans Administration surgeries found that complication rates increased from 5.6% to 14.0% in a dose-response manner with higher self-reports of alcohol use. [31] …”
Section: Readmissionsmentioning
confidence: 99%